2009
DOI: 10.3748/wjg.15.3032
|View full text |Cite
|
Sign up to set email alerts
|

Improving quality of colonoscopy by adding simethicone to sodium phosphate bowel preparation

Abstract: AIM:To evaluate the effectiveness of simethicone in enhancing visibility and efficacy during colonoscopy. METHODS:A prospective, double-blind, randomized, placebo-controlled study was conducted. One hundred and twenty-four patients were allocated to receive 2 doses of sodium phosphate plus 240 mg of tablet simethicone or placebo as bowel preparation. Visibility was blindly assessed for the amount of air bubbles and adequacy of colon preparation. Total colonoscopic time, side effects of the medication, endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 26 publications
(53 reference statements)
0
58
0
2
Order By: Relevance
“…Shaver et al 13 showed significantly better colon cleansing with simethicone and alluded to improvement in the right colon, a region more likely to be affected by adherent dense chyme. Tongprasert et al 1 showed that simethicone added to sodium phosphate improved visibility by diminishing bubbles. In the same study, there was a trend toward better colon cleansing with the addition of simethicone to sodium phosphate, though it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shaver et al 13 showed significantly better colon cleansing with simethicone and alluded to improvement in the right colon, a region more likely to be affected by adherent dense chyme. Tongprasert et al 1 showed that simethicone added to sodium phosphate improved visibility by diminishing bubbles. In the same study, there was a trend toward better colon cleansing with the addition of simethicone to sodium phosphate, though it did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2, 3 Bowel preparation may be inadequate in up to 25% of patients undergoing colonoscopy and may result in missed lesions during colorectal cancer screening. 4, 5, 6 Subsequently, reporting the adequacy of colon cleansing using one of the several available scales is an important measure of colonoscopy quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of 7 randomized trials comparing colonoscopy bowel purgative with or without the addition of simethicone, the overall effi cacy of colon preparation was comparable (OR, 2.06; 95% CI, 0.56-7.53; P =.27), despite a notable reduction in the presence of intraluminal bubbles (OR, 39.3; 95% CI, 11.4-135.9; P ≤.01) in the group receiving simethicone ( 172 ) . Th e dosage of simethicone varied between studies, ranging from 120-240 mg, or 45 mL of a 30% solution ( 76,(172)(173)(174) .…”
Section: Recommendationsmentioning
confidence: 99%
“…Regardless of the type of bowel preparation used, whether it is PEG or sodium phosphate-based, both types appear to have a similar level of bowel cleansing ability. Modifications of these two common types of bowel preparations, such as adding prokinetic agents to PEG [57,58] , or adding simethicone to sodium phosphate [59] , may provide some improvements in certain instances. However, it is recognized that factors other than the type of bowel cleansing agent used, have an equally, if not more, important role in influencing the quality of bowel preparation in patients undergoing colonoscopy.…”
Section: The Recent American Society For Gastrointestinalmentioning
confidence: 99%